2016
DOI: 10.1016/j.nutres.2016.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of canned citrus fruit meals increases human plasma β-cryptoxanthin concentration, whereas lycopene and β-carotene concentrations did not change in healthy adults

Abstract: Several studies suggest that β-cryptoxanthin has a greater plasma response from its common food sources than other carotenoids such as β-carotene and lycopene. The hypothesis of this study is that changes in plasma β-cryptoxanthin concentrations will be greater than changes in plasma β-carotene or lycopene concentrations even if these carotenoids are fed in a similar food matrix, such as citrus fruit. We tested this hypothesis by measuring changes in plasma concentrations of β-cryptoxanthin, lycopene, and β-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
(108 reference statements)
0
4
0
Order By: Relevance
“…There are a number of recently published clinical trials and meta‐analysis data revealing beneficial health effects of lycopene (Cicero & Colletti, ; Mahmoodnia, Mohammadi, & Masumi, ; Singh & Bagewadi, ; van Die et al., ). However, only few of them (Graff et al., ; Zhu, Gertz, Cai, & Burri, ) adequately address the issue of lycopene bioavailability in volunteers. As we shown above, the ingestion of lycopene does not necessarily translate into sustainable increase in circulating lycopene levels and rather reflects the type of nutraceutical formulation of lycopene used for supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…There are a number of recently published clinical trials and meta‐analysis data revealing beneficial health effects of lycopene (Cicero & Colletti, ; Mahmoodnia, Mohammadi, & Masumi, ; Singh & Bagewadi, ; van Die et al., ). However, only few of them (Graff et al., ; Zhu, Gertz, Cai, & Burri, ) adequately address the issue of lycopene bioavailability in volunteers. As we shown above, the ingestion of lycopene does not necessarily translate into sustainable increase in circulating lycopene levels and rather reflects the type of nutraceutical formulation of lycopene used for supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In a study which was conducted by Bailey et al, found that L-Citrulline supplementation improved O2 uptake kinetics and high-intensity exercise performance in humans [30]. In addition to that, it was approved that watermelon is rich source of many antioxidants such as β-carotene and lycopene which may increase nitric oxide bioavailability since they have been shown to blunt the scavenging of nitric oxide by superoxide [31]. It has also been reported by Tarazona et al and Cutrufello et al, that ingestion of watermelon juice can attenuate muscle soreness after completing intense exercise [14,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, in agreement with our study, serum concentrations of β-cryptoxanthin were higher than those of these carotenoids. Several studies suggest that β-cryptoxanthin is better absorbed from foods and is more bioavailable than other common carotenoids 10,11,13 . Moreover, clearance of β-cryptoxanthin from plasma is similar or faster than that of other carotenoids, such as β-carotene, lutein, and zeaxanthin 14,15 .…”
Section: Discussionmentioning
confidence: 99%